Present - Allen, Elizabeth (Newtown, NSW : Vagabond Press, 2017)
"A collection of stand-alone poems, certain themes and preoccupations bind the poems of Present together – family, friendship, loss and acceptance, the attempt to gain meaning from the experiences of daily life. The conversational and plain-spoken, if not always reliable, "I" of these poems attempts to express that which can’t be conveyed by traditional autobiographical modes of writing through experiments with form as well as voice. Allen uses humour and lucid observation to explore dark subject matter and the persistent question of distance; how in all relationships (including that of narrator and reader) we constantly juggle intimacy and connection with what is unfamiliar and strange." -- Publisher's website.
"This project has been assisted by the Australian Government through the Australia Council, its arts funding and advisory body." -- Publication details.
Keywords: Australian poetry -- 21st century; Australian; Poetry